Implikasi Good Corporate Governance Terhadap Persistensi Laba - Dian Maulita; Dien Sefty Framitha; Herman Wijaya; Burhanudin (Universitas Serang Raya, 2023)
ABSTRACT This research was conducted to examine the effect of managerial ownership, independent commissioners and audit committees on the earnings persistence of manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This study uses an associative method with a quantitative approach. The population in this study amounted to 144 companies and the sample was taken using purposive sampling technique as a data collection technique. The number of samples collected was 177 samples consisting of 59 manufacturing companies as the sample of this study for 3 years. Data analysis used in this research is descriptive statistics, classical assumption test, multiple linear regression analysis, and hypothesis testing. The data in this study were processed using the SPSS version 23 program. Partial results showed that managerial ownership had no effect on earnings persistence, independent commissioners had an effect on earnings persistence, audit committee had no effect on earnings persistence. Meanwhile, managerial ownership, independent commissioner and audit committee simultaneously affect earnings persistence